2011
DOI: 10.1007/s12032-011-0140-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive microRNA signature is associated with the diagnosis and prognosis of acute leukemia

Abstract: MicroRNAs (miRNAs) are of great importance in pathogenesis, diagnosis and prognosis of acute leukemia (AL). We studied five AL-related miRNAs to confirm the significance of these miRNAs in AL. Samples tested included acute myeloid leukemia (AML), 107 cases; acute lymphoblastic leukemia (ALL), 40 cases. Five AL-related miRNAs: miR-128, let-7b, miR-223, miR-181a and miR-155 expression were detected by qRT-PCR. Analysis showed that miRNA-128 expression was significantly higher in ALL (P<0.001). However, the let-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
3
25
1
1
Order By: Relevance
“…Earlier studies on AML have indicated changes in miRNA expression associated with outcome, such as miR-181a, miR181b, miR-124, miR-128-1, miR-194, miR-219-5p, miR-220a, miR-320, and miR-155 [Marcucci et al, 2008;Li et al, 2012;Zhu et al, 2012]. None of these miRNAs, however, existed in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…Earlier studies on AML have indicated changes in miRNA expression associated with outcome, such as miR-181a, miR181b, miR-124, miR-128-1, miR-194, miR-219-5p, miR-220a, miR-320, and miR-155 [Marcucci et al, 2008;Li et al, 2012;Zhu et al, 2012]. None of these miRNAs, however, existed in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have shown that miR-128(-3p) acts as an oncogene in malignancies such as acute leukemia, 24,25 breast cancer 13,[26][27][28] and lung cancer. 14 However, this miRNA has also been described to have tumor suppressive functions in other cancer entities (for an overview, refer to Online Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported in literature support a possible oncogenic function for miR-128-3p in ALL, as miR-128(-3p) was found to be significantly more highly expressed in ALL samples than in acute myeloid leukemia samples and normal control samples. 24,25,29 Possible mechanisms that could underlie miR-128-3p over-expression in T-ALL remain to be explored in further detail. Although to the best of our knowledge chromosomal aberrations or mutations specifically affecting miR-128 loci have not been reported so far, there is evidence that miR-128-3p expression could be affected by perturbed epigenetic regulation [hypomethylation of miR-128 promoter(s)] in T-ALL cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the expression of miRNA-181a in favorable prognosis group was significantly lower than in poor prognosis group. In FLT3-ITD mutation positive patients, the miRNA-155 expression was significantly higher than in the negative group (182). At this time only few studies have been performed on circulating miRNA in AL, but a recent study found that plasma levels of miRNA-92 might be a biomarker for acute myeloid leukemia (183).…”
Section: Llc Calin Et Almentioning
confidence: 99%